2017
DOI: 10.1016/s1878-6480(17)30036-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mean Transaortic Pressure Gradient on Long-Term Outcome in Patients with Severe Aortic Stenosis and Preserved Left Ventricular Ejection Fraction

Abstract: Background--Mean transaortic pressure gradient (MTPG) has never been validated as a predictor of mortality in patients with severe aortic stenosis. We sought to determine the value of MTPG to predict mortality in a large prospective cohort of severe aortic stenosis patients with preserved left ventricular ejection fraction and to investigate the cutoff of 60 mm Hg, proposed in American guidelines.Methods and Results--A total of 1143 patients with severe aortic stenosis defined by aortic valve area ≤1 cm 2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Our emergent patients' mean aortic gradient before the procedure was similar to Cribier’s patients [7] and higher than Debry’s [22]. More than half of emergent patients had values higher than 60 mmHg, a cut-off value proven to be associated with even greater mortality [24].…”
Section: Discussionmentioning
confidence: 64%
“…Our emergent patients' mean aortic gradient before the procedure was similar to Cribier’s patients [7] and higher than Debry’s [22]. More than half of emergent patients had values higher than 60 mmHg, a cut-off value proven to be associated with even greater mortality [24].…”
Section: Discussionmentioning
confidence: 64%
“…They found that MG > 60 mmHg at baseline was associated with greater risk of all-cause mortality than lower values, thereby justifying a separate hemodynamic classification. The higher MG also reflected the chronicity of the disease process [28] (see Figure 5).…”
Section: Normal Flow/very High Gradient or High Gradientmentioning
confidence: 97%
“…Once the AV Vmax is ≥5 m/s, survival is reduced even in the absence of symptoms ( 40 , 43 , 44 ). Similarly, a mean gradient ≥60 mmHg and an AVA ≤0.6 cm 2 are associated with extremely high event rates and largely correspond with an AV Vmax of 5 m/s ( 45 , 46 , 47 ). American guidelines advocate surgery in such patients even in the absence of symptoms (Class IIa indication) ( 6 ).…”
Section: Grading Of Severitymentioning
confidence: 99%